ASSESSMENT OF THE ACTIVITY OF RESIDENTS AND ECONOMIC GROWTH IN THE LAG TERRITORY - Mietule, Iveta; Zvaigzne, Anda; Čerpinska, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Research on participation in local action groups and their influence on the overall development of regional territories has become urgent in recent years, given the implementation of the Rural Development Programme LEADER as well as the interpretation of local action groups as a new research object in theoretical and empirical research studies. The research aim is to assess the activity of residents in the territory of a particular local action group and the overall development of the territory in the period 2009-2013. In 2014, 40 local action groups operated in Latvia. The present research focuses on the territory of a local action group and its residents. The research provides socio-economic characteristics of the territory (changes in the numbers of residents and business entities and in wages) as well as identifies and assesses the opinions of residents on motivations and hindering factors to starting up a business. A statistical analysis of resident survey data, employing the contingency method, shows that increase in the education level reduces one’s wish to start up a business and vice versa, whereas the age of the residents surveyed has no effect on their wish to start up a business.